Soybeans for the tropics - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
Singh, S.T., K.O. Rachie and K.E. Dashiell (eds.), 1987. Soybeans for the tropics: Research, production and utilization. IITA, 230 pp. ISBN 0471 91419 3